Improving the content of physical education classes students with visual impairments - Рядова [Liliana Riadovaia], Ліліана Олегівна; Шестерова [Ludmila Shesterova], Людмила Єгорівна (Slobozhanskyi Herald of Science and Sport, 2013)
<!--[if gte mso 9]> <![endif]--><!--[if gte mso 9]> <![endif]--><span style="font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman'; mso-fareast-font-family: Calibri; color: black; background: white; mso-ansi-language: UK; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="UK">The article presents the information about deviation in children’s health, on the basis of different sources analysis. The importance of physical education in the correction of deficiencies in this category of children, the analysis of existing programs of physical education of visually impaired. Consider some of the ways of correction of shortcomings in the development and physical fitness of children of school age caused by impaired. The study found that physical education plays a special role in the correction and compensation deviations. Identified some publications, devoted to the elaboration of programs and methodological approaches aimed at improvement of the content of the lessons of physical education of pupils with visual impairments. Insufficient <span style="font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman'; mso-fareast-font-family: Calibri; color: #2a2a2a; background: #F4F7FF; mso-ansi-language: UK; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="UK">investigation of the<span style="font-size: 12.0pt; line-height: 115%; font-family: 'Times New Roman'; mso-fareast-font-family: Calibri; color: black; background: white; mso-ansi-language: UK; mso-fareast-language: EN-US; mso-bidi-language: AR-SA;" lang="UK"> problem require the development of new ways to improve the physical development and training of children with impaired vision.<!--[if gte mso 9]> Normal 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]--><!--[if gte mso 9]> Normal 0 false false false <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if gte mso 10]> <![endif]-->